Spatially Dissociated Intracerebral Maps for Face- and House-Selective Activity in the Human Ventral Occipito-Temporal Cortex. (16th March 2020) - Hagen, Simen; Jacques, Corentin; Maillard, Louis; Colnat-Coulbois, Sophie; Rossion, Bruno; Jonas, Jacques
Abstract: We report a comprehensive mapping of the human ventral occipito-temporal cortex (VOTC) for selective responses to frequency-tagged faces or landmarks (houses) presented in rapid periodic trains of objects, with intracerebral recordings in a large sample ( N = 75). Face-selective contacts are three times more numerous than house-selective contacts and show a larger amplitude, with a right hemisphere advantage for faces. Most importantly, these category-selective contacts are spatially dissociated along the lateral-to-medial VOTC axis, respectively, consistent with neuroimaging evidence. At the minority of "overlap" contacts responding selectively to both faces and houses, response amplitude to the two categories is not correlated, suggesting a contribution of distinct populations of neurons responding selectively to each category. The medio-lateral dissociation also extends into the underexplored anterior temporal lobe (ATL). In this region, a relatively high number of intracerebral recording contacts show category-exclusive responses (i.e., without any response to baseline visual objects) to faces but rarely to houses, in line with the proposed role of this region in processing people-related semantic information. Altogether, these observations shed novel insight on the neural basis of human visual recognition and strengthen the validity of the frequency-tagging approach coupled with intracerebral recordings in epileptic patients to understand human brain function.